Magnetic resonance imaging texture analysis for quantitative evaluation of the mandibular condyle in juvenile idiopathic arthritis - Ricardo, Ana Lúcia Franco; Silva, Gabriel Araújo da; Ogawa, Celso Massahiro; Nussi, Amanda D.; Rosa, Catharina Simione de; Martins, Jaqueline Serra; Lopes, Sérgio Lúcio Pereira de Castro [UNESP]; Appenzeller, Simone; Braz-Silva, Paulo Henrique; Costa, Andre Luiz Ferreira (Springer Nature, 2022)
Objectives: Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease that affects the joints and other organs, including the development of the former in a growing child. This study aimed to evaluate the feasibility of texture analysis (TA) based on magnetic resonance imaging (MRI) to provide biomarkers that serve to identify patients likely to progress to temporomandibular joint damage by associating JIA with age, gender and disease onset age. Methods: The radiological database was retrospectively reviewed. A total of 45 patients were first divided into control group (23) and JIA group (22). TA was performed using grey-level co-occurrence matrix (GLCM) parameters, in which 11 textural parameters were calculated using MaZda software. These 11 parameters were ranked based on the p value obtained with ANOVA and then correlated with age, gender and disease onset age. Results: Significant differences in texture parameters of condyle were demonstrated between JIA group and control group (p < 0.05). There was a progressive loss of uniformity in the grayscale pixels of MRI with an increasing age in JIA group. Conclusions: MRI TA of the condyle can make it possible to detect the alterations in bone marrow of patients with JIA and promising tool which may help the image analysis.
Keywords: Bone; Computer-assisted diagnosis; Diagnostic imaging; Quantitative assessment; Radiomics